2016
DOI: 10.1007/s12041-016-0626-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin-10 (A1082G) gene polymorphism with oral squamous cell carcinoma in north Indian population

Abstract: The functional polymorphism A1082G in the gene (IL10) for interleukin-10 associated with risk of oral squamous cell carcinoma (OSCC). The present case-control study was to evaluate the possible association between IL10 A1082G gene and OSCC in north Indian population. Analysis of IL10 A1082G genotype in 232 OSCC cases and 221 healthy controls of comparable age, gender, smokers, tobacco chewing and alcohol consumption. IL10 A1082G status in cases and controls were evaluated by polymerase chain reaction and restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…At the same time, no obvious association between IL10 A1082G genotype and alcohol drinking was found (Tsai et al, 2014). Another case control study in India Hussain et al, (2016) revealed that among AA, AG, GG genotypes, an increase AG genotype cases as compared to control was found to be statistically significant. Thus the G allele of IL10 may be involved in the progression of OSCC.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…At the same time, no obvious association between IL10 A1082G genotype and alcohol drinking was found (Tsai et al, 2014). Another case control study in India Hussain et al, (2016) revealed that among AA, AG, GG genotypes, an increase AG genotype cases as compared to control was found to be statistically significant. Thus the G allele of IL10 may be involved in the progression of OSCC.…”
Section: Discussionmentioning
confidence: 95%
“…The etiology of a specific cancer might be associated with genetic variants. IL10 polymorphisms like A1082G/AA/AG/GG genotypes may not only contribute to differential expression levels of IL10 among individuals but may also lead the risk oral cancer susceptibility (Hussain et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Oral cancer has reported high prevalence rate globally, approximately 4 lakh new cases have reported annually with 39% death rate. [ 2 ] The survival rate is about 5 years for oral cancer patients. [ 3 ] The South Asian country, specifically Indian subcontinent, has a reported very high rate of oral cancer patients due to poor prognosis and delay in treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These cytokines, studied at both mutation and expression level, may serve as biomarkers of prognostic value. [90][91][92][93] The heterogeneity in cancer cells between and/or within patients makes it a complex disease to cure. 94 Identifying germ line mutations which may serve as biomarkers for predicting OC-susceptible individuals and/or who may respond differently to a particular cancer therapy is very important.…”
Section: Resultsmentioning
confidence: 99%